2018
DOI: 10.1371/journal.pone.0209112
|View full text |Cite|
|
Sign up to set email alerts
|

Taurine deficiency and dilated cardiomyopathy in golden retrievers fed commercial diets

Abstract: IntroductionGolden retrievers are over-represented in cases of taurine-deficient dilated cardiomyopathy and recently a surge in cases has prompted further investigation.ObjectiveTo describe the clinical, dietary, and echocardiographic features in golden retrievers diagnosed with taurine deficiency and dilated cardiomyopathy, and to determine specific dietary associations. A second aim was to determine the whole blood taurine concentrations in a representative sample of healthy golden retrievers.AnimalsTwenty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(127 citation statements)
references
References 39 publications
7
114
3
3
Order By: Relevance
“…Nutritionally mediated DCM has been described across a variety of species including dogs and is most historically linked to taurine deficiency [17][18][19][20][21][22][23][24][25][26][27]. Recent peerreviewed research on DCM in breeds that were not previously known to have a genetic etiology has raised concern about the relationship between diets with certain characteristics and the development of nutritionally-mediated DCM [28][29][30]. The Food and Drug Administration issued a warning and subsequently released data that identified dietary characteristics which were over-represented in consumer concern reports [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Nutritionally mediated DCM has been described across a variety of species including dogs and is most historically linked to taurine deficiency [17][18][19][20][21][22][23][24][25][26][27]. Recent peerreviewed research on DCM in breeds that were not previously known to have a genetic etiology has raised concern about the relationship between diets with certain characteristics and the development of nutritionally-mediated DCM [28][29][30]. The Food and Drug Administration issued a warning and subsequently released data that identified dietary characteristics which were over-represented in consumer concern reports [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Almost five decades ago, it was noted that a diet deficient of taurine led to the development of retinopathy in cats [15]. Subsequently, it was shown that cats and dogs with taurine deficiency developed cardiomyopathy [16,17]. Although the effects of taurine deficiency in humans are largely unknown, it is clear that infants depend on taurine for their neurodevelopment [18].…”
Section: Taurine Deficiencymentioning
confidence: 99%
“…Taurine (TAU) is a highly concentrated amino-acide with cyto-protective action in numerous tissues, especially in contractile ones such as heart (43). Oral TAU supplementation is cardio-protective, while depletion associates with dilated cardiomyopathy in several mammalian species (44,45).…”
Section: Discussionmentioning
confidence: 99%